The Relationship Between Spirituality and Depression of Elderly in Elderly Social Service - Nurnainah Nurnainah; Ismail Ismail; Wahyuni Wahyuni (GLOBAL HEALTH SCIENCE GROUP, 2020)
Depression is a mood disorder that becomes commonly happen in modern societies. The incidence of depression will increase in elderly with prevalence of 7.5% in women and 5.5% in men with an age range of 55-74 years old. One of the way to reduce depression in the elderly is by increasing their spirituality such as worship. The aim of the study was to determine the relationship between spirituality and depression in the elderly in Elderly Social Service Center (Pusat Pelayanan Sosial Lanjut Usia/ PPSLU) of Mappakasunggu Parepare in 2019. The type of this research was analytic descriptive using cross-sectional approach. This research was conducted at the Elderly Social Service Center (PPSLU) of Mappakasunggu Parepare in July 2019. The population in this study was 51 elderly who were depressed and were at the Elderly Social Service Center (PPSLU) of Mappakasunggu Parepare. The sampling technique used was total sampling. Data collection tool used was questionnaires with guided interviews to respondents. The data analysis was carried out using univariate and bivariate analysis. The results showed that among 7 respondents (13.7%) who had low spirituality, 6 (11.8%) of them had severe depression, among 24 respondents (47.1%) who had moderate spirituality 23 (45.1%) of them had moderate depression, and among 20 respondents (39.2%) who had high spirituality, 22 (43.1%) of them had mild depression. Menwhile, bivariate analysis showed that there was a significant relationship between spirituality and depression with a p-value = 0.000 (p <0.05). Based on this study, it can be concluded that the spirituality variable has a relationship with depression in the elderly. This research expected that the staff is able to provide and improve spirituality support so that the elderly can avoid depression.